Efektivitas Pembelajaran Eksploratif tentang Konsep dan Proses Fisika pada Dinamika Harian Iklim Mikro di Permukaan Lahan Bervegetasi dan Tidak Bervegetasi - Natasha Khaterina Marselina Etwiory; Treesje Katrina Londa; Djeli Alvi Tulandi (Program Studi Pendidikan Fisika Jurusan Fisika Fakultas Matematika, Ilmu Pengetahuan Alam, dan Kebumian (FMIPAK), Universitas Negeri Manado, 2022)
Explorative learning about the concepts and processes of physics in the daily dynamics of the microclimate on the surface of vegetated and non-vegetated soil is an example of the physics learning process by utilizing the natural surroundings as a learning object. The purpose of this researh was to determine the effectiveness of explorative learning in analyzing the concepts and processes of physics in the daily dynamics of the microclimate on the surface of vegetated and non-vegetated land. This research used a pre-experimental method one group pretest-posttest design. The research subjects are third semester students of Physics Education, Manado State University 2021/2022. Data collection is in the form of observation tables/exploratory fromats. After obtaining the data, the research results were statistically processed using the SPSS 22.0 application for windows. The pretest average result was 47.80 and increased to 89.70 in the posttest average. Obtaining N-Gain scores from student, there are 8 students in the high N-Gain category with a percentage of 80% and 2 students in the medium N-Gain category with a percentage of 20%. The average result of the N-Gain percentage of 10 students is 80.15%. The results of this reseacrh indicate that explorative learning is effectively used in exploring physical concepts and processes in the daily dynamics of the microclimate on vegetated and non-vegetated soil surfaces.